The Role of Computed Tomography in Differentiation of Coronavirus Pneumonia, its Complications and Comorbidities. Case Reports - V. S. Petrovichev; A. V. Melekhov; M. A. Sayfullin; I. G. Nikitin (Архивъ внутренней медицины, 2020)
Background: computer tomography (CT) features of COVID-19, their temporal changes and differences from other pulmonary (viral and bacterial pneumonia) and non-pulmonary diseases are well described in recent publications. The prevalence and characteristics of signs of concomitant problems that could be identified at chest CT are less studied.Aim: to analyze the prevalence and characteristics of chest CT features of COVID-19, its complications and comorbidities.Methods: retrospective analysis of CT and clinical data of 354 patients hospitalized with suspected COVID at April and May of 2020.Results: 962 CT scans were analyzed (3 (2-3) scans per patient). First CT was performed at 8 (5-11) day of sickness. Several roentgenological scenarios could be highlighted: patients with coronavirus pneumonia (n=295; 83%); with combination of COVID-19 and another pathology (n=36; 10%); with complications of COVID-19 (n=12; 3%); with alternative pathology (n=2; 1%); without any pathological signs (n=9; 3%). Several cases, illustrating CT signs of coronavirus pneumonia, its complications and comorbidities are reported.Conclusion: CT possibilities are not limited to detect typical COVID-19 signs, it also helps to differentiate pulmonary and other thoracis pathology.